The impacts of the final phase of transition to IFRS in Brazil - Pires, Clênia de Oliveira; Decourt, Roberto Frota (Review of Business Management, 2015)
Objective – This article aims to measure the impacts of the final phase of mandatory convergence to IFRS on net income, in equity and total assets of Brazilian publics companies. Design/methodology/approach – It is applied to the inverse of Gray (1980)’s Conservatism Index – which allows you to compare the results between different accounting systems – to determine the impacts of the transition between the two phases of the convergence process in Brazil, covered by the law 11,638 and their CPCs. It was compared the 2009 financial results disclosed in BR GAAP and IFRS. Findings – The results show that the final stage of mandatory convergence to IFRS led to significant increases in both net income and the shareholders’ equity of the companies analysed: a mean increase of about 21% in earnings and about 11% in equity, as well as generating an increase, though somewhat less significant, about 7%, the total assets. Practical implications – This research helped to improve understanding of the impacts of convergence of Brazilian accounting to the international standard; as well as to assist business managers and users of financial information, especially those from the capital markets, regulators and academia, about the ultimate effects on the results reported in 2011, after the implementation of the final phase of convergence. Originality/value – The fiscal year of 2009 was a special year for understanding the impact of accounting system in the financial results disclosed in Brazil. The Brazilian publics companies reported their results in BR GAAP and IFRS and this research analysed and compare both reports and improve understanding of the impacts of convergence of Brazilian accounting to the international standard.